Development and Evaluation of a Residential Plumbing Mock-Up - Oting, Eduardo Saliim (Journal of Technical Education and Training, 2026)
The insufficiency of physical learning materials in Technical and Vocational Education and Training (TVET) often results in a purely theoretical approach that fails to equip students with industry-essential functional skills. This research developed and validated a residential plumbing mock-up as an instructional tool for the Plumbing NC II program at Mountain Province State University. Employing a sequential exploratory mixed-methods approach based on the ADDIE framework, the study first identified pedagogical gaps through thematic analysis of teacher and student perspectives, highlighting resource insufficiency and declining student interest. In response, a multi-functional residential plumbing setup was developed, incorporating water supply and Drain Waste and Vent (DWV) lines in strict accordance with the Revised Plumbing Code of the Philippines. The validation test produced a very high level of content validity (S-CVI/Ave = 0.94). The level of design quality was rated moderately to highly effective (6.19/7.0). The inter-rater reliability showed a fair level of consistency (ICC = 0.67). The level of acceptability tests among the students produced a Very Good level, specifically with regard to design (4.83/5.0). Additionally, a consideration of the STEEP (Social, Technological, Economic, Environmental, and Political) factors further established the importance of the usage of the proposed product for water conservation and the compliance with water policies. The conclusion of the validation test thus supports the proposed product as a very appropriate tool to strategically address the theoretical deficits present in the curriculum. The proposed product should thus be fully integrated into the curriculum and the replication of this developmental methodology to other technical disciplines to address the scarcity of resources.